2000
DOI: 10.1007/s001270050236
|View full text |Cite
|
Sign up to set email alerts
|

Political change and course of schizophrenia in East Germany, 1984-1994

Abstract: There is no evidence that political change in East Germany negatively affected the course of longterm schizophrenia as assessed by hospitalisations. If consistent medical care is provided, characteristics of the political system may have less impact on the course of schizophrenia than is sometimes assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…This innovative mental heath system was established in a creative style in order to settle fears and insecurities between various communities as well as cater to a fragmented and lower income community, while introducing an element of self-determination in personal mental health care. Although it may be expected that political tensions may exacerbate severe mental illnesses such as schizophrenia, if consistent psychiatric care is provided it has been suggested that characteristics of political upheaval may result in less impact on the course of the illness (Priebe & Broker, 2000).…”
Section: Clinical Observations Stemming From “Supermarket” Activitymentioning
confidence: 99%
“…This innovative mental heath system was established in a creative style in order to settle fears and insecurities between various communities as well as cater to a fragmented and lower income community, while introducing an element of self-determination in personal mental health care. Although it may be expected that political tensions may exacerbate severe mental illnesses such as schizophrenia, if consistent psychiatric care is provided it has been suggested that characteristics of political upheaval may result in less impact on the course of the illness (Priebe & Broker, 2000).…”
Section: Clinical Observations Stemming From “Supermarket” Activitymentioning
confidence: 99%
“…Das Ausmaû der Hospitalisierung wurde mit Hilfe eines von Lavik[17] und Tansella[18] entwickelten Hospitalisierungsindex (HI) bestimmt. Der bereits in früheren Studien in modifizierter Form verwendete HI[19,20,21] wurde wie folgt berechnet: Anzahl der vollstationären Behandlungstage dividiert durch die Gesamtzahl der Tage des Beobachtungszeitraumes[22]. Der HI wurde für die fünfjährigen Zeiträume vor und nach November 1989 zusammengefasst.…”
unclassified